Kinetics and Mechanism of Oxidation of Glutamic Acid by N-Bromophthalimide in Aqueous Acidic Medium - N. M. I. Alhaji; S. Sofiya Lawrence Mary (E-Journal of Chemistry)
The kinetics of oxidation of glutamic acid (Glu) with N-bromophthalimide (NBP) was studied in perchloric acid medium at 30 °C by potentiometric method. The reaction is first order each in NBP and glutamic acid and is negative fractional order in [H+]. Addition of KBr or the reaction product, phthalimide had no effect on the rate. Similarly variation of ionic strength of the medium did not affect the rate of the reaction. Also the rate increased with decrease in dielectric constant of the reaction medium. The thermodynamic parameters were computed from Arrhenius and Eyring plots. A suitable mechanism consistent with the kinetic results has been proposed.